2017
DOI: 10.1038/srep42329
|View full text |Cite
|
Sign up to set email alerts
|

The spectral and spatial distribution of light pollution in the waters of the northern Gulf of Aqaba (Eilat)

Abstract: The urbanization of the shores of the Gulf of Aqaba has exposed the marine environment there, including unique fringing coral reefs, to strong anthropogenic light sources. Here we present the first in situ measurements of artificial nighttime light under water in such an ecosystem, with irradiance measured in 12 wavelength bands, at 19 measurement stations spread over 44 square km, and at 30 depths down to 30-m depth. At 1-m depth, we find downwelling irradiance values that vary from 4.6 × 10−4 μW cm−2 nm−1 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 63 publications
4
83
0
Order By: Relevance
“…The fourth is an under-examined side effect of constant light exposure on the onset of increased Daphnia reproduction under certain levels of salinity and/or acidity stress that are considered otherwise unfavourable for exponential reproduction. Light pollution effects, in terms of artificial light, sky glow and interference with daylight-night-time patterns, which increasingly affect aquatic ecosystems and ecological interactions [34,106], are becoming a serious concern associated with urbanisation and industrialised zones with increasing human population around the globe [30,34,107110]. The far-reaching effects of extended light exposure [34] may not only lead to changes in vital phototactic behaviours with disruptive impacts on the aquatic system [30,34], but may also extend to how zooplankton respond to a cocktail of stressors [77,111].…”
Section: Resultsmentioning
confidence: 99%
“…The fourth is an under-examined side effect of constant light exposure on the onset of increased Daphnia reproduction under certain levels of salinity and/or acidity stress that are considered otherwise unfavourable for exponential reproduction. Light pollution effects, in terms of artificial light, sky glow and interference with daylight-night-time patterns, which increasingly affect aquatic ecosystems and ecological interactions [34,106], are becoming a serious concern associated with urbanisation and industrialised zones with increasing human population around the globe [30,34,107110]. The far-reaching effects of extended light exposure [34] may not only lead to changes in vital phototactic behaviours with disruptive impacts on the aquatic system [30,34], but may also extend to how zooplankton respond to a cocktail of stressors [77,111].…”
Section: Resultsmentioning
confidence: 99%
“…Tamir, Lerner, Haspel, Dubinsky, and Iluz () measured underwater spectra at 19 locations at different depths in the coastal waters of the Gulf of Eilat, Israel with a profiling multispectral radiometer with 12 spectral channels between 300 and 900 nm and mapped the extend of ALAN for these waters. They showed that wavelengths at 589 and 443 nm can still be detected in depths greater than 10 m at a great distance from the shore.…”
Section: Light Pollution and Aquatic Systemsmentioning
confidence: 99%
“…They used a commercial DSLR camera with a fisheye lens to acquire all‐sky and vertical plane hemispherical images and a small single‐channel SQM photometer for long‐term measurements. Jechow, Kolláth, Lerner, et al () later showed that the DSLR method can also be used from a moving boat, taking measurements in the Gulf of Eilat near some measurement spots of Tamir et al ().…”
Section: Light Pollution and Aquatic Systemsmentioning
confidence: 99%
See 2 more Smart Citations